Serum magnesium, bone–mineral metabolism markers and their interactions with kidney function on subsequent risk of peripheral artery disease: the Atherosclerosis Risk in Communities Study. Issue 11 (19th March 2020) - Menez, Steven; Ding, Ning; Grams, Morgan E; Lutsey, Pamela L; Heiss, Gerardo; Folsom, Aaron R; Selvin, Elizabeth; Coresh, Josef; Jaar, Bernard G; Matsushita, Kunihiro
Abstract: Background: Few studies have investigated the association of magnesium levels with incident peripheral artery disease (PAD) despite emerging evidence of magnesium contributing to vascular calcification. Moreover, no data are available on whether the magnesium–PAD relationship is independent of or modified by kidney function. Methods: A cohort of 11 839 participants free of PAD in the Atherosclerosis Risk in Communities Study at Visit 2 (1990–92) was studied. We investigated the association of serum magnesium and other bone–mineral metabolism markers [calcium, phosphorus, intact parathyroid hormone (iPTH) and intact fibroblast growth factor-23] with incident PAD using multivariable Cox proportional hazards regression. Results: Over a median of 23 years, there were 471 cases of incident PAD. The hazard ratio for incident PAD in Quartile 1 (<1.5 mEq/L) versus Quartile 4 (>1.7 mEq/L) of magnesium was 1.96 (95% confidence interval 1.40–2.74) after adjustment for potential confounders. Lower magnesium levels were associated with greater incidence of PAD, particularly in those with estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m 2 ( n = 11 606). In contrast, the association was largely flat in those with eGFR <60 mL/min/1.73 m 2 ( n = 233) with P-for-interaction 0.03. Among bone–mineral metabolism markers, only higher iPTH showed an interaction with kidney function (P-for-interaction 0.01) and iPTH >65 pg/mL was significantly related to PAD only in those with eGFR <60 mL/min/1.73 m 2 . Conclusions: Lower magnesium was independently associated with incident PAD, but this association was significantly weaker in those with reduced kidney function. In contrast, higher iPTH levels were particularly related to PAD risk in this clinical population.